Isolation of the Escherichia coli leader peptidase gene and effects of leader peptidase overproduction in vivo. - Date, T (1981)
The only covalent modifications known to accompany protein insertion into membranes or protein secretion are glycosylation and the proteolytic removal of an NH2-terminal leader (signal) sequence. This latter reaction is catalyzed by leader peptidase, a constitutive, membrane-bound proteinase. We now report the identification of a plasmid-bearing strain of Escherichia coli that overproduces leader peptidase 4- to 6-fold. This strain grows normally and shows an unaltered polypeptide composition of inner ad outer membranes. The leader peptidase gene has been subcloned and transferred from this plasmid to the multicopy plasmid pBR322, yielding a new plasmid (pTD101). Strains transformed by pTD101 have a 30-fold increase in leader peptidase. We have studied the effect of leader peptidase overproduction on the insertion of newlymade M13 phage coat protein into the plasma membrane of infected cells. The overproducer strain, when infected by M13 phage, shows a dramatic acceleration in the conversion of procoat (a cytoplasmic precursor form) to coat (an integral, transmembrane protein). Thus the leader peptidase that converts M13 procoat to coat in vitro can catalyze this reaction in vivo as well.